The Effect Of Star Endorser Attraction, Credibility, And Expertise - Cheng -Wen Lee; Taufiqquddin Ande (Green Publisher Indonesia, 2022)
Background: Advertising media are frequently employet as promotial media to disseminate information about produducts. The aspect of celebrity endorser's profile is their level of attractiveness, another aspect their credibility and domain knowledge. Purpose: This study aims to examine the effect of attractiveness, credibility, and expertise of celebrity endorsers on purchasing decisions. Method : Experimental research techniques are 59 participants were utilize as the experimental and 60 participants as the control. The data for this study were derived from responses of participants who had received various treatments prior to the distribution of the questionnair. Result : The variable attraction (X1) of the celebrity endorser to the purchase decision (Y) has a value of 0.011 and a significant t-count value of 4.891 at = 0.05 (one-way) t-table value of 1.986. The t-count value > the t-table. The credibility variable (X2) of the celebrity endorser to the purchase decision (Y) has a value of 0.085 and a significant t-count value of 3.426 at = 0.05 (one-way) table t value of 1.986. The t-count value > the t-table. The skill variable (X3) of the celebrity endorser to the purchase decision (Y) has a value of 0.051 and a t-count value of 2.416 is significant at = 0.05 (one-way) t-table value 1986. T-count value > t -table. Conclusion: The results in this study showed that the celebrity endorser variable (X1), credibility variable (X2) and skill variable (X3) had a positive and significant correlation effect on purchasing decisions (Y).